“AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (Studi Wilayah Desa Kecamatan Pemalang Kabupaten Pemalang) Tahun 2015 S/D 2016” - Anggit Wahyu Pambudi., 14.05.52.0236; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
This study aims to determine accountability of village fund allocation management in three stages: planning, implementation, and accountability stages. The study was conducted in 13 villages of Pemalang sub-district with a total sample of 67 village officials who have authority in village financial management especially ADD. Associated village officials are village head, secretary, treasurer, head section and head of affairs. The results show that the village financial management has been running well according to the Miniser of Home Affairs Regulation No. 113 of 2014 and the Regulation of Regent Pemalang No. 58 year 2015. At the planning stage of village goverment is open to the community and involve the community in planning activities. The implementation stage is carried out by the implementing team of activity that the development activities are orderly and in accordance with the standards. And the responbility of the village head is responsible for the use of the budget to the local goverment, village councils, and the community. Keywords: Accountability, Village Fund Allocation, Planning Stage, Implementation Phase, Responsibility Stage